Removal of ammonium nitrogen from wastewater by tertiary treatment - Šarko, Julita; Mažeikienė, Aušra (International Conference “Environmental Engineering”, 2023)
Ammonium nitrogen present in treated wastewater effluent can cause eutrophication. Wastewater treatment plants do not always meet the strict requirements for the residual total nitrogen concentration – 10 mg/L in the treated wastewater. Additional wastewater treatment is recommended for higher nitrogen removal efficiency achievement. One of the ways to remove nitrogen compounds from wastewater is filtration through sorbents filter media. Zeolite is used to remove nitrogen compounds from water. Zeolite is known for its high surface area and high porosity. Zeolite adsorbs part of organic compounds and ammonium ions, so their concentration in the filtrate decreases. An ammonium nitrogen concentration was reduced by filtering wastewater through sorbents filter media during the experiment in real conditions. Concentrations of treated wastewater pollutants, filtration rate, efficiency of zeolite sorbent to remove ammonium nitrogen from the wastewater were measured and evaluated. Experiment results showed that ammonium nitrogen was effectively removed by zeolite sorbent (removal efficiency 66–99%), from wastewater by tertiary treatment.